Recessions and instable estimates of potential output - Dovern, Jonas; Zuber, Christopher (Discussion paper series, 2017)
This paper analyzes how the OECD revises potential output (PO) estimates after recessions. We show that downward revisions are substantial and mostly driven by supply shocks while PO estimates do not significantly react to demand shocks. In addition, revisions are partly caused by avoidable mismeasurement of PO before recessions. In particular, we show that the length of the preceding boom and pre-recession values of the current account balance and credit volumes are predictors of post-recession PO revisions. Our results call for improved methods for estimating PO and provide evidence against the existence of substantial hysteresis effects of demand shocks.
Keywords: OECD; Graue Literatur; Hysterese; Trend